Substance use in a sexual context: The association of sex-related substance use motives with substance choice and use behaviors - Elliott, Jennifer C. (J Subst Use, 2020)
BACKGROUND. Substance use before sex is associated with riskier behaviors. Sex-related substance use motives may explain pre-sex substance use. We explored what sex-related motives are associated with alcohol versus drug use, and which motives underlie heavier use. METHODS. A sample of 936 participants (50% male, 80% White) completed an Internet survey about sexuality. Those who drank before sex (n=657) reported on six sex-related drinking motives; those who used drugs before sex (n=271) reported on six (parallel) sex-related drug use motives. The frequency of endorsement of each motive between drinkers and drug users was compared with z-distributions. Logistic regressions assessed whether motives were associated with substance use frequency and intoxication before sex. RESULTS. Substance use to relax and to get a sex partner to use were more commonly endorsed for alcohol than drugs; substance use to improve performance and enhance experience were more commonly endorsed for drugs. Most motives were associated with alcohol frequency and intoxication before sex. None were associated with drug frequency; some were associated with drug intoxication. CONCLUSIONS. Alcohol was generally used to facilitate sex, and drugs to enhance sex. Sex-related drinking motives were associated with drinking before sex; sex-related drug use motives were less predictive.